Privatization experiences in the European Union - Köthenbürger, Marko; Sinn, Hans-Werner; Whalley, John (CESifo seminar series., 2006)
In this work, experts evaluate the varied outcomes of privatization experiences in Austria, Denmark, Finland, France, Germany, Ireland, Italy, the Netherlands, Spain, and the UK.